Elementary School PJOK Teachers' Perceptions of the Independent Learning - Mardiana; Badaru, Benny; Arfanda, Poppy Elisano; Arimbi; Hudain, Muh. Adnan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This quantitative descriptive study aims to understand how PJOK SD teachers view independent learning in the district. South Polombangkeng, Takalar district. The population in this study consisted of 32 elementary school PJOK teachers in Takalar Regency. We collected data using techniques like observation, questionnaires, interviews, and documentation. We used descriptive analysis as a data analysis technique. In more detail, the results show that in the